Patterns of play associated with success in international rugby sevens - Higham, D. G.; Hopkins, W. G.; Pyne, D. B.; Anson, J. M. (International Journal of Performance Analysis in Sport, 2014)
Understanding the relationships between annual mean performance indicators and team ranking in the IRB Sevens World Series should inform long-term tactical approaches to competition. In this study we characterised these relationships using official data for each of the 12 core teams during the men's IRB Sevens World Series between 2008/2009 and 2011/2012. Mean values, typical within-team variability and typical between-team differences were derived from the four annual World Series mean values for 23 performance indicators. Linear mixed modelling was employed to quantify the effect of an increase in performance indicator values (from typically low to typically high) on logarithmically-transformed series ranking within and between teams. Ten indicators had clear substantial between-team effects (2- to 3-fold differences) on team ranking, but only five had clear substantial within-team effects (~1.5-fold changes). Tries scored and tries conceded had the strongest effects on ranking. Tactics that improved team ranking were based on increasing ball retention in line-outs and the breakdown, turning over possession more frequently in opposition rucks, and pressuring the opposition in their territory by kicking fewer short restarts. These findings confirm the intuitive importance of some common performance indicators and provide valuable novel insights for tactical planning.